2018
DOI: 10.4103/jips.jips_80_17
|View full text |Cite
|
Sign up to set email alerts
|

A study on the evaluation of bite force, prosthetic and nutritional status in adult cleft patients in Kolkata

Abstract: Context: Altered orofacial morphology and poor dental status affects the dietary intake of cleft patient, making susceptible to nutritional imbalance. Oral health care planning for this population is impossible without the evaluation of stomatognathic functional status as well as prosthetic and nutritional status and need. Aims: The aim of this study was to evaluate prosthetic status and prosthetic treatment need, bite force and nutritional status, in adult cleft patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…To measure the bite force, a U-shaped transducer equipped with a strain gauge as used in previous studies (FLA-5–11, Tokyo Sokki Kenkyujo Co., Ltd., Tokyo, Japan). [ 15 ] The machine was calibrated by the unique forces of the universal testing machine (K-21046, Walter-Bai Co., Lohningen, Switzerland). The metal head of the machine was covered with 2-mm-thick rubber pads that prevented tooth damage when applying the force.…”
Section: Methodsmentioning
confidence: 99%
“…To measure the bite force, a U-shaped transducer equipped with a strain gauge as used in previous studies (FLA-5–11, Tokyo Sokki Kenkyujo Co., Ltd., Tokyo, Japan). [ 15 ] The machine was calibrated by the unique forces of the universal testing machine (K-21046, Walter-Bai Co., Lohningen, Switzerland). The metal head of the machine was covered with 2-mm-thick rubber pads that prevented tooth damage when applying the force.…”
Section: Methodsmentioning
confidence: 99%
“…[ 7 8 9 10 ] Various methods have been used to assess the efficiency of masticatory system, including the measurement of bite force and masticatory efficiency. [ 11 ] The results of some previous investigations showed a linear relationship between electromyographic activity potentials and direct bite force measurements. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Flores-Orozco et al 21 have demonstrated that MP does not seem to be related to NS and BMI in a nonsyndromic population. Contrary to these results, Bera et al 23 have shown that BF is reduced in a cleft population and NS was observed to be significantly higher "at risk" in cleft than in noncleft group.…”
Section: Discussionmentioning
confidence: 66%